A web and software-based approach blending social networks for online Qur’anic arabic learning - Abdullah, Matin Saad; Pathan, Al Sakib Khan; Al-Shaikhli, Imad Fakhri Taha (© 2017 Zarka Private Univ., 2018)
This article was published in the International Arab Journal of Information Technology [© 2017 Zarka Private Univ.] The Journal's website is at: https://www.scopus.com/sourceid/19500157821?origin=recordpage